Interpreting a major component from a mixed DNA profile with an unknown number of minor contributors. (May 2019) - Bille, Todd; Weitz, Steven; Buckleton, John S.; Bright, Jo-Anne
Highlights: 147 mixtures of 3–5 contributors with at least one major contributor were examined. N assigned during interpretation was varied from the experimental value. LR s were assigned for 614 true donors and 147, 268 false donors. LRs for majors in mixture proportions at least twice that of the minor were unchanged. LR s for minor contributors are reduced when the incorrect N is assumed. Abstract: Modern interpretation strategies typically require an assignment of the number of contributors ( N ) to a DNA profile. This can prove to be a difficult task, particularly when dealing with higher order mixtures or mixtures where one or more contributors have donated low amounts of DNA. Differences in the assigned N at interpretation can lead to differences in the likelihood ration ( LR) . If the number of contributors cannot reasonably be assigned, then an interpretation of the profile may not be able to be progressed. In this study, we investigate mixed DNA profiles of varying complexity and interpret them altering the assigned N . We assign LR s for true- and non- contributors and compare the results given different assignments of N over a range of mixture proportions. When a component of a mixture had a proportion of at least 10%, a ratio of at least 1.5:1 to the next highest component, and a DNA amount (as determined by STRmix™) of at least 50 rfu, the LR of the component for a true contributor was not significantly affected by varying N and was therefore suitable for interpretation and the assignment of an LR . LR s produced for minor contributors were found to vary significantly as the assigned N was changed. These heuristics may be used to identify profiles suitable for interpretation.